Karakteristik dan Pemanfaatan Plasma Nutfah Ubi Jalar (Ipomoea batatas (L.) Lam) di Pulau Moa, Kabupaten Maluku Barat Daya - Maitimu, Marselina; Parera, Djemli F; Hehanussa, Meitty L (JURNAL BUDIDAYA PERTANIAN, 2021)
Genetic resources exploration and conservation of sweet potato germplasm is very important to respond to the increased fooddemand in the future. Therefore, the use of superior varieties with high yields represents one of the solutions. To produce superiorvarieties, gene sources are needed that are suitable for the breeding targets. As an initial step, this study was conducted to characterizesweet potato germplasms and to collect accessions or local varieties in Moa Island. Using the purposive sampling method observationand description were conducted based on characters of vine and root parts of the plants, and eleven accessions were found, those werePatatas Kuning A Patatas Kuning B, Patatas Madu A, Patatas Madu B, Patatas Maroke A, Patatas Maroke B, Patatas Maroke C,Patatas Gila-gila A, Patatas Gila-gila B, Patatas Gila-gila C, and Patatas Telor. Cluster analysis was performed using 20morphological characters, and a dendogram was generated which showed the degrees of similarities among the accessions. Theresults of this study showed that sweet potato in Moa Island diverse based on shoot and tuber morphological characteristics. Basedon observations of morphological and other visual characteristics, preliminary descriptions of the eleven accessions found wereproduced.